The Influence of Internship Experience, Self-Efficacy, and Work Motivation on Work Readiness of Bangka Belitung University Students - Putri, Dhea Amanda; Reniati; Wahyudin, Nanang (International Journal of Economics, Business, and Entrepreneurship, 2024)
As communications and technology advance, preparing students for a competitive job market is critical. This research analyzes three key factors that influence students' work readiness: internship experience, self-confidence, and work motivation. The research uses a quantitative approach with descriptive statistics. A sample of 193 participants was selected through cluster sampling from Bangka Belitung University students class of 2020. The independent variables were internship experience, self-ability, and work motivation, while the dependent variable was work readiness. Multiple linear regression analysis was used to test the data. The results show that internship experience and self-efficacy have a positive and significant influence on students' work readiness. Work motivation shows a positive but not significant influence. Taken together, these three factors show a positive and significant combined influence on the work readiness of students class of 2020 at Bangka Belitung University.